Anodic Nanotubular/porous Hematite Photoanode for Solar Water Splitting: Substantial Effect of Iron Substrate Purity - Lee, Chong-Yong; Wang, Lei; Kado, Yuya; Killian, Manuela; Schmuki, Patrik (ChemSusChem, 2014)
Anodization of iron substrates is one of the most simple and effective ways to fabricate nanotubular (and porous) structures that could be directly used as a photoanode for solar water splitting. Up to now, all studies in this field focused on achieving a better geometry of the hematite nanostructures for a higher efficiency. The present study, however, highlights that the purity of the iron substrate used for any anodic-hematite-formation approach is extremely important in view of the water-splitting performance. Herein, anodic self-organized oxide morphologies (nanotubular and nanoporous) are grown on different iron substrates under a range of anodization conditions, including elevated temperatures and anodization supported by ultrasonication. Substrate purity has not only a significant effect on oxide-layer growth rate and tube morphology, but also gives rise to a ninefold increase in the photoelectrochemical water-splitting performance (0.250 vs. 0.028mA cm-2 at 1.40V vs. reversible hydrogen electrode under AM1.5 100mW cm-2 illumination) for 99.99 % versus 99.5 % purity iron substrates of similar oxide geometry. Elemental analysis and model alloys show that particularly manganese impurities have a strong detrimental effect on the water-splitting performance.
EAM Import::2019-03-13